A forgotten history, a marginalized community: Biographical narratives of Ethiopian Jews, former activists in underground organizations during the civil war in Ethiopia, 1974–1991. Issue 1 (18th July 2017) - Ratner, David
Abstract: Despite a proliferation of studies concerning Ethiopian Jews (formerly known as "Beta Israel") and their lives while still in Ethiopia, a topic that has not been studied enough is their lives during the turbulent period of the 1974 revolution and the civil war that followed (ending 1991). According to most existing (Israeli) literature, this group was completely cut off from these events, or at most passively affected by them. The present study, based on 17 in‐depth interviews with Ethiopian‐born Israelis, shows that some members of the community were indeed deeply involved in these historical events, as political activists and/or military rebels in one of two major political parties: the TPLF and the EPRP. After a short historical introduction, the study discusses the central themes that emerged from the interviews: (1) the interviewees' deep identification with universal and contemporary ideology, (2) their deep solidarity with Ethiopia and with the organizations they belonged to, (3) abandonment of revolutionary ideology and politics after arrival in Israel. The central argument in the concluding part is that this chapter in the community's history was forgotten because it did not accord with the Ethiopian Jews' intended role as reinforcement of the official Zionist narrative of the negation of exile. This oblivion meant that the community was constructed in the Israeli public imagination as pre‐modern, detached from modern ideologies and characterized by a very limited worldview.